1993
DOI: 10.1213/00000539-199303000-00028
|View full text |Cite
|
Sign up to set email alerts
|

Memory Facilitation by Posttraining Exposure to Halothane, Enflurane, and Isoflurane in ddN Mice

Abstract: The effect of low and high concentrations of halothane, enflurane, and isoflurane on posttraining memory function was studied in male ddN mice. Mice were trained to escape an aversive electric foot shock as an unconditioned stimulus within 3 s after being exposed to light and a buzzer as a conditioned stimulus. Immediately after training (first session: 30 trials), the animals were exposed to halothane, enflurane, or isoflurane for 120 min and then were tested again on the avoidance task (second session: 30 tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Although patients often regain consciousness quickly after general anesthesia with volatile anesthetics, there is a growing concern of volatile anesthetic safety in recent years. Cognitive impairment in rats can be detected at least 3 weeks after being exposed to volatile anesthetics [7,8], although improvement of cognitive functions after volatile anesthetic exposure in rodents also has been reported [7,9,10]. Volatile anesthetics increase activated caspase 3 expression and β-amyloid peptide (Aβ) production in mouse brains [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although patients often regain consciousness quickly after general anesthesia with volatile anesthetics, there is a growing concern of volatile anesthetic safety in recent years. Cognitive impairment in rats can be detected at least 3 weeks after being exposed to volatile anesthetics [7,8], although improvement of cognitive functions after volatile anesthetic exposure in rodents also has been reported [7,9,10]. Volatile anesthetics increase activated caspase 3 expression and β-amyloid peptide (Aβ) production in mouse brains [11].…”
Section: Introductionmentioning
confidence: 99%
“…Such a memory-enhancing effect in young animals had been demonstrated previously with the use of a nonspatial task 22 h after anesthesia administration. 12 A comparative study of rats aged 7 or 60 days showed that 4 h of isoflurane caused a permanent deficit of hippocampal-dependent but not hippocampalindependent learning and memory in 7-day-old rats, whereas 60-day-old animals showed a long-term improvement in spatial reference memory. 13 Concerning the acquisition of new tasks, recent studies have demonstrated learning impairment 24 h and 2 weeks after anesthesia in aged rats, 14 whereas adult rats showed improved learning.…”
mentioning
confidence: 99%
“…This indings are supported by preclinical studies, which suggest that isolurane anaesthesia administered at clinically relevant doses causes longterm cognitive impairment in unoperated animals [33][34][35]. However, other studies point towards an enhancement of the cognitive functions after anaesthesia inhalation [36][37][38].…”
Section: Introductionmentioning
confidence: 79%